Development of Small-Scale Integrated Farming Design: towards Optimizing Agricultural Learning Media - Ni Kadek Ema Sustia Dewi; Arif Umami (SEAS (Sustainable Environment Agricultural Science), 2023)
Learning about integrated farming could be done by visiting site locations directly. This is a problem for universities that are located in urban areas. The distance of the integrated agricultural location from the campus often raises a significant cost burden. Therefore, providing a learning model around the university would be more efficient, and students could interact and practice directly. The design concept was compiled based on a literature review. The design was produced by direct observation at Condongcatur experimental garden, then continued SWOT analysis. The design was created using software based on the information gathered. The design development included a general description of the experimental garden, landscape biophysical aspect, concept planning, and design. The resulting design was then validated by experts descriptively using a questionnaire. Meanwhile, user acceptance was measured qualitatively through an interview. Based on the results obtained, theoretically, a small-scale integrated farming design has been successfully compiled and met the requirements to be developed as an agricultural learning model. The design also received a good response from the management, which would then be followed up in the long-term development plan of the experimental garden.